Sistem Pengurusan Inventori dalam Talian Kedai Bundle - Muqri Amin Mohd Shamsuddin; Mohamad Aizi Salamat (Applied Information Technology And Computer Science, 2021)
Inventory is the largest current asset of a company’s other organizations. Good inventory management is important for the costs incurred by a company with a certain number of inventories in stock. Inventory management difficulties will result in a business. In the service sector, the inability of a company to supply something in the inventory, will cause the journey of the organization to come to a halt. Details of companies that use too much, holding costs may occur a significant difference between profit and loss. Good and effective inventory management is necessary for inventory costs with a reduction in the amount of inventory in the company. The management study conducted at Kedai Bundle Amin which is a store that sells classic items and needs improvement in inventory management and control methods as well as events record the available data. Therefore, an online inventory management system is proposed to replace the manual system or improve the existing system and the problems faced by the company in a systematic and orderly manner. The method used by Amin Bundlle Shop in ordering volatile goods and stock will not be left up to the minimum level. Therefore, the development of Amin Store Inventory Management System proposes to manage the inventory of the store. The proposed system uses Adobe Macromedia Dreamweaver version 6 software to design the system with the help of PhpMyAdmin software version 7.7 for use in data storage to the database.